A solid-state electrolyte membrane with a lattice oxygen in-situ activation-organic covalent anchoring-supramolecular network synergistic interface and a preparation method thereof
By combining in-situ activation of lattice oxygen with synergistic interface design of organic covalently anchored supramolecular networks, the interface and bulk transport bottlenecks of garnet-type oxide solid electrolytes are solved, achieving high ionic conductivity, low interfacial impedance, and long cycle stability, making it suitable for all-solid-state lithium-ion batteries.
Patent Information
- Application Number
- CN202610407928.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-03-31
- Publication Date
- 2026-06-26
AI Technical Summary
Existing technologies cannot effectively solve the multiple bottleneck problems of garnet-type oxide solid electrolytes in the interface and bulk phase transport, including poor interface contact, lithium dendrite growth, high grain boundary resistance and poor cycle stability, which leads to a decline in the performance of lithium-ion batteries.
By employing a synergistic interface design of lattice oxygen in-situ activation, organic covalent anchoring, and supramolecular network, oxygen vacancies are introduced through plasma treatment to form Zr-OP and La-OP covalent bonds, and a supramolecular network containing UPy quadruple hydrogen bonds and disulfide bonds is constructed to achieve self-healing and flexible contact of the electrolyte membrane.
It significantly improves lithium-ion transport rate, reduces interface impedance, enhances the self-healing ability and mechanical properties of electrolyte membrane, extends cycle life, adapts to different battery specifications, and broadens battery application scenarios.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid electrolyte membrane technology, specifically to a solid electrolyte membrane with a lattice oxygen in-situ activation-organic covalent anchoring-supramolecular network synergistic interface and its preparation method. Background Technology
[0002] As a core component of next-generation energy storage, lithium-ion batteries are seeing increasing demand in new energy vehicles, portable electronic devices, and large-scale energy storage power stations. High safety, high energy density, and long cycle life have become the core goals of their technological development. Traditional liquid lithium-ion batteries suffer from problems such as flammability, leakage, and poor high-temperature stability due to organic electrolytes, which can easily lead to thermal runaway, explosions, and other safety accidents. Furthermore, the presence of the electrolyte limits further improvements in battery energy density. Solid-state electrolytes, with their leak-proof, non-flammable, and wide electrochemical window characteristics, have become the core material for solving the safety hazards of liquid batteries and constructing high-energy-density all-solid-state lithium-ion batteries. Among them, garnet-type oxide solid electrolytes (represented by LLZO and LLZTO) have achieved room-temperature ionic conductivity of up to 10⁻⁶. -3 Its outstanding advantages, such as S / cm level, excellent chemical stability, and no obvious side reactions with lithium metal anode, have made it a research hotspot in the field of solid electrolytes.
[0003] However, garnet-type oxide solid electrolytes still face multiple bottlenecks in practical applications, particularly in interfacial and bulk transport. Their rigid inorganic ceramic nature leads to poor compatibility with electrode materials. The core problems are concentrated in the following three aspects: 1. Poor solid-solid interface contact and extremely high interfacial impedance: Garnet oxides are rigid ceramic materials, and their contact with lithium metal anode and cathode active materials is a point-to-point hard contact, resulting in a large number of interfacial voids and an interfacial impedance that can reach thousands of Ω·cm. 2 This becomes the main obstacle to lithium-ion cross-interface transport, severely reducing the rate performance and cycle performance of the battery. 2. Poor surface lithium affinity, which easily induces lithium dendrite puncture: The poor wettability between the native surface of garnet electrolyte and lithium metal prevents lithium metal from spreading evenly on the electrolyte surface, resulting in local current density concentration. Lithium dendrites are prone to grow along grain boundaries or interface gaps and puncture the electrolyte membrane, causing internal short circuits in the battery and leading to safety failure. 3. Grain boundary impurity phase enrichment and bulk phase transport obstruction: During the high-temperature sintering process of garnet electrolyte, lithium element volatilization is prone to occur, and low ionic conductivity impurities such as La2Zr2O7 and Li2CO3 are easily generated at the grain boundaries. These impurities become "roadblocks" for lithium ion transport between grains, resulting in a high proportion of grain boundary resistance and a decrease in overall bulk phase ion transport efficiency. At the same time, although traditional ultra-high temperature sintering (>1200℃) can improve the electrolyte density, it will further aggravate lithium volatilization and impurity phase formation, forming a contradiction between "density improvement and impurity phase control".
[0004] To address these issues, researchers have developed various modification strategies for garnet-type electrolytes, mainly including physical coating, introduction of inorganic intermediate layers, and elemental doping. However, existing technologies all have significant limitations and have failed to fundamentally achieve synergistic optimization of bulk, grain boundary, and interface properties. 1. Physical coating modification: Physical coating of garnet particles with polymers and other materials can improve the interfacial contact between electrolyte and electrode to a certain extent. However, the polymer layer itself has low ionic conductivity and only physical adsorption with the oxide surface, resulting in weak bonding. During battery cycling, it is prone to debonding and peeling due to volume stress, leading to rapid degradation of interfacial performance. 2. Inorganic Intermediate Layer Modification: Constructing inorganic intermediate layers such as Al2O3, ZnO, and Au on the electrolyte surface through sputtering, coating, etc., can improve the surface lithiophilicity. However, this method is complex and costly. Furthermore, the rigid inorganic intermediate layer introduces a new solid-solid interface, which cannot buffer the volume change stress of the electrode during battery cycling and is prone to interfacial microcracks. At the same time, some intermediate layer materials have side reactions with lithium metal, affecting the long-term stability of the battery. 3. Element doping modification: By doping with elements such as Ta, Nb, and Al to regulate the garnet lattice structure, the bulk ionic conductivity can be effectively improved. However, this strategy only optimizes the electrolyte bulk phase and has limited ability to regulate grain boundary impurities. Furthermore, it cannot improve the interfacial contact problem between the electrolyte and the electrode. Grain boundaries and interfaces remain the core bottleneck for lithium-ion transport. 4. Limitations of single interface modification: Existing technologies mostly focus on solving single problems such as "bulk phase modification", "interface contact improvement" and "lithophile enhancement", failing to coordinate the design of lattice oxygen active sites, grain boundary transport channels and electrode-electrolyte interface contacts of garnet electrolytes at the atomic / molecular level. As a result, the performance of bulk phase, grain boundary and interface cannot be optimized simultaneously, making it difficult to meet the practical application requirements of all-solid-state lithium-ion batteries.
[0005] In summary, developing a synergistic modification strategy that enables lattice activation, grain boundary optimization, and interface adaptive buffering to construct a garnet-type solid electrolyte membrane with high ionic conductivity, low interfacial impedance, strong structural stability, and self-healing capabilities is key to promoting the industrial application of all-solid-state lithium-ion batteries and is also a technical challenge that urgently needs to be solved in this field. Summary of the Invention
[0006] The technical problem to be solved by this invention is to overcome the shortcomings of the prior art and provide a solid electrolyte membrane with a synergistic interface of in-situ activation of lattice oxygen, organic covalent anchoring, and supramolecular network, as well as its preparation method. The solid electrolyte membrane with the synergistic interface of in-situ activation of lattice oxygen, organic covalent anchoring, and supramolecular network integrates high ionic conductivity, low interfacial impedance, high critical current density, self-healing ability, excellent mechanical properties, and long cycle stability. It effectively solves the core technical bottleneck of garnet-type oxide solid electrolytes and provides key material and technical support for the industrial application of all-solid-state lithium-ion batteries. It has important industrial application value and scientific research significance.
[0007] The technical solution of this invention is as follows: On one hand, the present invention provides a method for preparing a solid electrolyte membrane with a lattice oxygen in-situ activated-organic covalent anchored-supramolecular network synergistic interface, comprising the following steps: Synthesis of S1 Ta / Nb co-doped LLZO: S1-1 Raw material mixing: In an argon glove box, according to the stoichiometric ratio Li 6.5 La3Zr 1.5 Ta 0.3 Nb 0.2 O 12 Weigh out Li2CO3, La2O3, ZrO2, Ta2O5, and Nb2O5, ball mill them together, remove the solvent by rotary evaporation, vacuum dry and sieve the resulting slurry; S1-2 Pre-calcination: The sieved powder is heated to 900-1000℃ in a muffle furnace and held for 4-5 hours to remove CO2 and residual organic matter; the pre-calcined powder is then ball-milled again to refine the particles. S1-3 Forming and Sintering: The powder is dry-pressed into discs, heated to 1150-1200℃ in air atmosphere, and sintered for 12-14h; cooled in the furnace to obtain dense LLZTO ceramic discs; the ceramic discs are coarsely crushed and then ball-milled to obtain LLZTO powder. S2 lattice oxygen activation treatment: LLZTO powder is spread in a quartz boat, placed in a plasma-enhanced chemical vapor deposition reaction chamber, and a mixture of Ar and O2 gas is introduced for plasma treatment. Construction of S3 phosphonic acid anchoring layer: Aminopropylphosphonic acid (NH2-C3H6-PO3H2) and glycidyl methacrylate (GMA) were dissolved in anhydrous THF, and triethylamine was added as a catalyst. The reaction was carried out at 50-60℃ for 6-8 h to obtain a phosphonic acid derivative containing double bonds (denoted as GMA-PA). The LLZTO powder activated in step S2 was dispersed in ethanol, and the phosphonic acid derivative containing double bonds was added. The mixture was refluxed and stirred at 60-70℃ for 8-9 h. After the reaction was completed, the mixture was centrifuged, washed with ethanol to remove unreacted anchoring molecules, and then vacuum dried to obtain phosphonic acid anchored modified LLZTO powder. Construction of S4 supramolecular self-healing network: S4-1 Supramolecular Polymer Synthesis: (1) Preparation of prepolymer: Polyethylene glycol (PEG) and isophorone diisocyanate (IPDI) are dissolved in anhydrous THF, and the catalyst dibutyltin dilaurate (DBTDL) is added. The reaction is carried out at 60-70℃ for 4-5 h to obtain a -NCO-terminated prepolymer solution. (2) Introducing UPy: Dissolve UPy-NH2 in DMSO, add the above prepolymer solution dropwise, and continue the reaction at 60-70℃ for 6-8h to obtain polyurethane containing UPy units; (3) Introducing disulfide bonds: Weigh 2,2′-dithiodiethanol (DTDE) and add it to the reaction system. React at 60-70℃ for 4-5 h to obtain supramolecular polymers and introduce disulfide bonds into the polymer backbone; Preparation of S4-2 composite membrane: The supramolecular polymer is dissolved in anhydrous THF to obtain a polymer solution; the phosphonic acid-anchored modified LLZTO powder obtained in step S3 is added to the above polymer solution and stirred to allow the polymer to fully penetrate and encapsulate the modified particles; a photoinitiator is added and stirring is continued to obtain a slurry; the slurry is poured into a polytetrafluoroethylene mold, cast into a film, and vacuum dried to remove the solvent; the dried film is irradiated under ultraviolet light to cause the residual double bonds in the polymer to crosslink, enhance the network stability, and obtain a solid electrolyte membrane.
[0008] Preferably, in step S2, the volume ratio of Ar:O2 in the mixed gas is 4:1, the flow rate of the mixed gas is 50-60 sccm, the working pressure is 50-60 Pa, the radio frequency power is 150-160 W, and the plasma treatment time is 30-60 min.
[0009] Preferably, in step S3, the mass-to-volume ratio of aminopropylphosphonic acid, glycidyl methacrylate, anhydrous THF, and triethylamine is (5-10) g: (4-6) g: (50-60) mL: (0.5-1) mL.
[0010] Preferably, in step S3, the phosphonic acid derivative containing double bonds is 10-15% of the mass of the LLZTO powder activated in step S2.
[0011] Preferably, in step (1), the mass-to-volume ratio of polydiethanol, isophorone diisocyanate, catalyst dibutyltin dilaurate, and anhydrous THF is (200-250g):(40-50)g:1g:(1000-1200)mL.
[0012] Preferably, in step (2), the mass-to-volume ratio of UPy-NH2, DMSO and the catalyst dibutyltin dilaurate in step (1) is (30-40) g: (200-300) mL: 1 g.
[0013] Preferably, in step (3), the mass ratio of 2,2′-dithiodiethanol to the catalyst dibutyltin dilaurate in step (1) is (15-20):1.
[0014] Preferably, in step S4-2, the mass ratio of supramolecular polymer, phosphonic acid-anchored modified LLZTO powder to initiator is (10-15):(90-100):1.
[0015] Preferably, in step S4-2, the photoinitiator is 2-hydroxy-2-methylphenylacetone.
[0016] On the other hand, the present invention provides a solid electrolyte membrane with a synergistic interface of lattice oxygen in situ activation, organic covalent anchoring, and supramolecular network, which is prepared by the above-described method for preparing a solid electrolyte membrane with a synergistic interface of lattice oxygen in situ activation, organic covalent anchoring, and supramolecular network.
[0017] This invention constructs a gradient solid-state electrolyte interface structure through the synergistic design of in-situ activation of lattice oxygen, organic covalent anchoring, and supramolecular networks. This overcomes the technical bottlenecks of traditional garnet-type oxide electrolytes, such as poor interfacial contact, insufficient lithium wettability, high grain boundary resistance, and poor cycle stability. Simultaneously, it endows the electrolyte membrane with self-healing and high mechanical strength properties. Compared with existing technologies, it possesses the following significant advantages: 1. This invention utilizes Ar / O2 mixed plasma low-temperature treatment to precisely introduce controllable concentrations of oxygen vacancies onto the surface of LLZTO garnet particles, transforming the surface inert lattice oxygen into an activated state. These oxygen vacancies act as "active springboards" for lithium-ion transport, reducing the activation energy for lithium-ions to cross the surface barrier through a local electric field effect, thus significantly improving the lithium-ion transport rate between the ceramic bulk phase and the surface. Simultaneously, the plasma treatment does not damage the bulk LLZTO lattice structure, preserving the advantage of high ionic conductivity in the bulk phase. This allows the prepared solid electrolyte membrane to achieve a room-temperature ionic conductivity of over 0.85 mS / cm, far superior to unmodified garnet ceramic electrolytes and traditional composite electrolytes.
[0018] 2. This invention utilizes phosphonic acid derivatives to react with Zr particles on the activated LLZTO surface. 4+ La 3+ Stable Zr-OP and La-OP covalent bonds are formed to construct a monomolecular-level covalent anchoring layer. Compared with the van der Waals forces of traditional physical coating, chemical bonding increases the bonding strength between the organic layer and inorganic ceramic particles by an order of magnitude. During battery cycling, it can withstand the volumetric expansion and contraction stress of the electrode and avoid the peeling and shedding of the interface layer. At the same time, the anchoring layer has a short chain structure, which will not block the lithium-ion transport channels and can also provide effective grafting sites for the upper supramolecular network, realizing a continuous transition of the inorganic-organic interface.
[0019] 3. This invention introduces a supramolecular polymer network containing UPy quadruple hydrogen bonds and dynamic disulfide bonds. Through the rapid room-temperature recombination of hydrogen bonds and the thermally induced dynamic exchange of disulfide bonds, the electrolyte membrane is endowed with excellent self-healing properties. The self-healing efficiency can reach 96% in 2 hours at 60°C, which can quickly repair interfacial microcracks and microdefects generated during battery cycling. At the same time, the flexible supramolecular network transforms the traditional "hard-to-hard" rigid contact between garnet electrolyte and electrode into a "rigid-flexible" adaptive contact, which can expand and contract in real time with the electrode volume change, always maintaining a tight fit with the electrode, eliminating interfacial voids, and reducing the interfacial impedance with lithium metal to 42 Ω·cm. 2 The following significantly reduces the problem of localized current density concentration, effectively suppresses the growth and penetration of lithium dendrites, and increases the critical current density of the electrolyte membrane to 2.8 mA / cm². 2 The lithium symmetric battery has a cycle life of over 4000 hours.
[0020] 4. The core innovation of this invention lies in the triple synergistic effect of the lattice oxygen activation layer, the covalent anchoring layer, and the supramolecular network layer. It achieves integrated optimization of the bulk phase, grain boundaries, and electrode-electrolyte interface of garnet electrolyte at the atomic / molecular level: the lattice oxygen activation layer solves the surface barrier problem of "lithium ions being unwilling to enter", the covalent anchoring layer solves the bonding stability problem of "easy detachment of the interface layer", and the supramolecular network layer solves the interface adaptation problems of "no buffering of volume stress" and "difficult repair of micro-damage". The synergy of the three makes lithium ions move without significant resistance in the entire transport path of "ceramic bulk phase-activation layer-anchoring layer-supramolecular network-electrode", realizing continuous, low-resistance, and stable cross-interface transport, fundamentally solving the core defect of existing technologies that cannot simultaneously optimize the performance of bulk phase, grain boundaries, and interfaces.
[0021] 5. The solid electrolyte membrane prepared by this invention combines the high ionic conductivity of inorganic ceramics with the flexibility of organic supramolecular polymers. Compared with the brittle characteristics of pure garnet ceramic electrolytes, this composite electrolyte membrane has a tensile strength of 8.5 MPa and an elongation at break of 65%, exhibiting good flexibility and machinability, and can be adapted to the needs of battery manufacturing of different specifications. At the same time, in the all-solid-state battery cycle test, the capacity retention rate reaches 93% after 500 cycles at 0.5C rate, which is far superior to the traditional PEO / LLZTO composite electrolyte and unmodified LLZTO electrolyte, solving the problem of rapid performance decay of garnet-type electrolytes and significantly improving the long-cycle reliability of all-solid-state lithium-ion batteries.
[0022] 6. The triple synergistic interface constructed in this invention has no obvious chemical side reactions with the lithium metal anode and ternary cathode (such as NCM811), and the supramolecular network and covalent anchoring layer can effectively isolate the direct contact between the electrolyte and the electrode, avoiding the reaction between the grain boundary impurities and the electrode; at the same time, the electrolyte membrane has a wide electrochemical window, which can be adapted to high-voltage cathode materials, breaking through the limitations of traditional electrolytes on battery systems and expanding the application scenarios of all-solid-state lithium-ion batteries in new energy vehicles, large-scale energy storage, portable electronic devices and other fields.
[0023] In summary, the solid electrolyte membrane prepared by this invention, which features a synergistic interface of in-situ activation of lattice oxygen, organic covalent anchoring, and supramolecular network, integrates high ionic conductivity, low interfacial impedance, high critical current density, self-healing ability, excellent mechanical properties, and long-term cycle stability. It effectively solves the core technical bottleneck of garnet-type oxide solid electrolytes, providing key material and technical support for the industrial application of all-solid-state lithium-ion batteries, and has significant industrial application value and scientific research significance. Detailed Implementation
[0024] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Example 1 The preparation method of the solid electrolyte membrane with the lattice oxygen in-situ activation-organic covalent anchoring-supramolecular network synergistic interface in this embodiment includes the following steps: Synthesis of S1 Ta / Nb co-doped LLZO S1-1 Raw material mixing: In an argon glove box, according to the stoichiometric ratio Li 6.5 La3Zr 1.5 Ta 0.3 Nb 0.2 O12 Weigh out 7.2g Li₂CO₃, 16.3g La₂O₃ (pre-calcined at 900℃ for 2h to remove moisture), 6.2g ZrO₂, 2.2g Ta₂O₅, and 0.9g Nb₂O₅. Place all raw materials and 200g zirconia grinding beads (5mm diameter) into a 500mL zirconia ball mill jar. Add 100mL isopropanol as a dispersant and ball mill at 400rpm for 6h, reversing the mill every 30min. Remove the slurry, remove the solvent by rotary evaporation at 80℃, dry under vacuum at 100℃ for 12h, and pass through a 200-mesh sieve.
[0026] S1-2 Pre-calcination: Place the powder in a magnesium oxide crucible and heat it to 900℃ in a muffle furnace at a rate of 3℃ / min, hold for 5 hours to remove CO2 and residual organic matter. Then, ball mill the pre-calcined powder again for 4 hours (under the same conditions as step S1-1) to refine the particles.
[0027] S1-3 Forming and Sintering: The powder was dry-pressed into discs with a diameter of 20 mm (approximately 1 mm thick) at 200 MPa. The green blanks were placed in a magnesium oxide crucible covered with masterbatch powder and sintered at 1150 °C for 14 h under air atmosphere at a rate of 5 °C / min. After furnace cooling, dense LLZTO ceramic discs were obtained. The ceramic discs were coarsely crushed in an agate mortar and then ball-milled at 500 rpm for 6 h to obtain LLZTO powder.
[0028] S2 lattice oxygen activation treatment Take 5g of LLZTO powder and spread it evenly in a quartz boat. Place it in the plasma-enhanced chemical vapor deposition reaction chamber and introduce a mixed gas of Ar and O2 (Ar:O2 volume ratio = 4:1). The total gas flow rate is 50sccm, the working pressure is 50Pa, the radio frequency power is 150W, and the plasma treatment time is 30min.
[0029] S3 phosphonic acid anchoring layer construction Anchored molecule synthesis: 5g of aminopropylphosphonic acid and 4.3g of glycidyl methacrylate were dissolved in 50mL of anhydrous THF, and 0.5mL of triethylamine was added as a catalyst. The reaction was carried out at 50℃ for 8h to obtain a phosphonic acid derivative containing double bonds (denoted as GMA-PA).
[0030] Surface anchoring: Take 5g of activated LLZTO powder and disperse it in 100mL of ethanol. Add 0.5g of GMA-PA and reflux at 60℃ for 9h.
[0031] Washing and drying: After the reaction is completed, centrifuge and wash three times with ethanol to remove unreacted anchoring molecules. Dry under vacuum at 60°C for 12 hours to obtain phosphonic acid-anchored modified LLZTO powder (denoted as P-LLZTO).
[0032] Construction of S4 supramolecular self-healing network S4-1 Supramolecular Polymer Synthesis (1) Preparation of prepolymer: Weigh 10g of polyethylene glycol (PEG, molecular weight 2000) and 2.2g of isophorone diisocyanate, dissolve them in 50mL of anhydrous THF, add 0.05g of DBTDL, and react at 70℃ for 4h to obtain a -NCO-terminated prepolymer solution.
[0033] (2) Introducing UPy: Weigh 1.5g of UPy-NH2, dissolve it in 10mL of DMSO, add the above prepolymer solution dropwise, and continue to react at 60℃ for 8h to obtain polyurethane containing UPy units (denoted as PU-UPy).
[0034] (3) Introducing disulfide bonds: Weigh 0.8g of 2,2′-dithiodiethanol and add it to the reaction system. React at 60℃ for 5h to introduce disulfide bonds into the polymer backbone. The final product is denoted as PU-UPy-SS.
[0035] Preparation of S4-2 composite membrane 0.5 g of PU-UPy-SS polymer was dissolved in 9.5 g of anhydrous THF to obtain a 5 wt.% polymer solution. 4.5 g of P-LLZTO powder was weighed and added to the polymer solution. The mixture was magnetically stirred for 12 h to allow the polymer to fully penetrate and encapsulate the modified particles. 0.05 g of the photoinitiator 2-hydroxy-2-methylphenylacetone was added, and stirring was continued for 30 min. The resulting slurry was poured into a polytetrafluoroethylene mold and cast into a film. The film was then vacuum dried at 50 °C for 6 h to remove the solvent. The dried film was then subjected to ultraviolet light (365 nm, power 10 mW / cm²). 2 Irradiation for 10 minutes under a light source causes the residual double bonds in the polymer to crosslink, enhancing network stability and yielding a solid electrolyte membrane, denoted as PU-LLZTO.
[0036] Example 2 The preparation method of the solid electrolyte membrane with the lattice oxygen in-situ activation-organic covalent anchoring-supramolecular network synergistic interface in this embodiment includes the following steps: Synthesis of S1 Ta / Nb co-doped LLZO S1-1 Raw material mixing: In an argon glove box, according to the stoichiometric ratio Li 6.5 La3Zr 1.5 Ta 0.3 Nb 0.2 O 12Weigh out 7.2g Li₂CO₃, 16.3g La₂O₃ (pre-calcined at 900℃ for 2h to remove moisture), 6.2g ZrO₂, 2.2g Ta₂O₅, and 0.9g Nb₂O₅. Place all raw materials and 200g zirconia grinding beads (5mm diameter) into a 500mL zirconia ball mill jar. Add 100mL isopropanol as a dispersant and ball mill at 400rpm for 6h, reversing the mill every 30min. Remove the slurry, remove the solvent by rotary evaporation at 80℃, dry under vacuum at 100℃ for 12h, and pass through a 200-mesh sieve.
[0037] S1-2 Pre-calcination: Place the powder in a magnesium oxide crucible and heat it to 950°C in a muffle furnace at a rate of 3°C / min, holding for 4.5 hours to remove CO2 and residual organic matter. Then, ball mill the pre-calcined powder again for 4 hours (under the same conditions as step S1-1) to refine the particles.
[0038] S1-3 Forming and Sintering: The powder was dry-pressed into discs with a diameter of 20 mm (approximately 1 mm thick) at 200 MPa. The green blanks were placed in a magnesium oxide crucible covered with masterbatch powder and sintered at 1150 °C at a rate of 5 °C / min in air atmosphere for 13 h. After furnace cooling, dense LLZTO ceramic discs were obtained. The ceramic discs were coarsely crushed in an agate mortar and then ball-milled at 500 rpm for 6 h to obtain LLZTO powder.
[0039] S2 lattice oxygen activation treatment Take 5g of LLZTO powder and spread it evenly in a quartz boat. Place it in the plasma-enhanced chemical vapor deposition reaction chamber and introduce a mixed gas of Ar and O2 (Ar:O2 volume ratio = 4:1). The total gas flow rate is 55sccm, the working pressure is 55Pa, the radio frequency power is 155W, and the plasma treatment time is 45min.
[0040] S3 phosphonic acid anchoring layer construction Anchored molecule synthesis: 8g of aminopropylphosphonic acid and 5g of glycidyl methacrylate were dissolved in 55mL of anhydrous THF, and 0.6mL of triethylamine was added as a catalyst. The reaction was carried out at 55℃ for 7h to obtain a phosphonic acid derivative containing double bonds (denoted as GMA-PA).
[0041] Surface anchoring: Take 5g of activated LLZTO powder and disperse it in 100mL of ethanol. Add 0.6g of GMA-PA and reflux at 65℃ for 8.5h.
[0042] Washing and drying: After the reaction is completed, centrifuge and wash three times with ethanol to remove unreacted anchoring molecules. Dry under vacuum at 60°C for 12 hours to obtain phosphonic acid-anchored modified LLZTO powder (denoted as P-LLZTO).
[0043] Construction of S4 supramolecular self-healing network S4-1 Supramolecular Polymer Synthesis (1) Preparation of prepolymer: Weigh 11g of polyethylene glycol (PEG, molecular weight 2000) and 2g of isophorone diisocyanate, dissolve them in 55mL of anhydrous THF, add 0.05g of DBTDL, and react at 65℃ for 4.5h to obtain a -NCO-terminated prepolymer solution.
[0044] (2) Introduction of UPy: Weigh 1.6g of UPy-NH2, dissolve it in 13mL of DMSO, add the above prepolymer solution dropwise, and continue to react at 65℃ for 7h to obtain polyurethane containing UPy units (denoted as PU-UPy).
[0045] (3) Introducing disulfide bonds: Weigh 0.8g of 2,2′-dithiodiethanol and add it to the reaction system. React at 65℃ for 4.5h to introduce disulfide bonds into the polymer backbone. The final product is denoted as PU-UPy-SS.
[0046] Preparation of S4-2 composite membrane 0.6 g of PU-UPy-SS polymer was dissolved in 9.5 g of anhydrous THF to obtain a 5 wt.% polymer solution. 4.8 g of P-LLZTO powder was weighed and added to the polymer solution. The mixture was magnetically stirred for 12 h to allow the polymer to fully penetrate and encapsulate the modified particles. 0.05 g of the photoinitiator 2-hydroxy-2-methylphenylacetone was added, and stirring was continued for 30 min. The resulting slurry was poured into a polytetrafluoroethylene mold and cast into a film. The film was then vacuum dried at 50 °C for 6 h to remove the solvent. The dried film was then subjected to ultraviolet light (365 nm, power 10 mW / cm²). 2 Irradiation for 10 minutes under a light source causes the residual double bonds in the polymer to crosslink, enhancing network stability and yielding a solid electrolyte membrane, denoted as PU-LLZTO.
[0047] Example 3 The preparation method of the solid electrolyte membrane with the lattice oxygen in-situ activation-organic covalent anchoring-supramolecular network synergistic interface in this embodiment includes the following steps: Synthesis of S1 Ta / Nb co-doped LLZO S1-1 Raw material mixing: In an argon glove box, according to the stoichiometric ratio Li 6.5 La3Zr 1.5 Ta 0.3 Nb 0.2 O 12Weigh out 7.2g Li₂CO₃, 16.3g La₂O₃ (pre-calcined at 900℃ for 2h to remove moisture), 6.2g ZrO₂, 2.2g Ta₂O₅, and 0.9g Nb₂O₅. Place all raw materials and 200g zirconia grinding beads (5mm diameter) into a 500mL zirconia ball mill jar. Add 100mL isopropanol as a dispersant and ball mill at 400rpm for 6h, reversing the mill every 30min. Remove the slurry, remove the solvent by rotary evaporation at 80℃, dry under vacuum at 100℃ for 12h, and pass through a 200-mesh sieve.
[0048] S1-2 Pre-calcination: Place the powder in a magnesium oxide crucible and heat it to 1000℃ in a muffle furnace at a rate of 3℃ / min, hold for 4 hours to remove CO2 and residual organic matter. Then, ball mill the pre-calcined powder again for 4 hours (under the same conditions as step S1-1) to refine the particles.
[0049] S1-3 Forming and Sintering: The powder was dry-pressed into discs with a diameter of 20 mm (approximately 1 mm thick) at 200 MPa. The green blanks were placed in a magnesium oxide crucible covered with masterbatch powder and sintered at 1200 °C at a rate of 5 °C / min in air atmosphere for 12 h. After furnace cooling, dense LLZTO ceramic discs were obtained. The ceramic discs were coarsely crushed in an agate mortar and then ball-milled at 500 rpm for 6 h to obtain LLZTO powder.
[0050] S2 lattice oxygen activation treatment Take 5g of LLZTO powder and spread it evenly in a quartz boat. Place it in the plasma-enhanced chemical vapor deposition reaction chamber and introduce a mixed gas of Ar and O2 (Ar:O2 volume ratio = 4:1). The total gas flow rate is 60sccm, the working pressure is 60Pa, the radio frequency power is 160W, and the plasma treatment time is 60min.
[0051] S3 phosphonic acid anchoring layer construction Anchored molecule synthesis: 10g of aminopropylphosphonic acid and 6g of glycidyl methacrylate were dissolved in 60mL of anhydrous THF, and 1mL of triethylamine was added as a catalyst. The reaction was carried out at 60℃ for 6h to obtain a phosphonic acid derivative containing double bonds (denoted as GMA-PA).
[0052] Surface anchoring: Take 5g of activated LLZTO powder and disperse it in 100mL of ethanol. Add 0.75g of GMA-PA and reflux at 70℃ for 8h.
[0053] Washing and drying: After the reaction is completed, centrifuge and wash three times with ethanol to remove unreacted anchoring molecules. Dry under vacuum at 60°C for 12 hours to obtain phosphonic acid-anchored modified LLZTO powder (denoted as P-LLZTO).
[0054] Construction of S4 supramolecular self-healing network S4-1 Supramolecular Polymer Synthesis (1) Preparation of prepolymer: Weigh 12.5g of polyethylene glycol (PEG, molecular weight 2000) and 2.5g of isophorone diisocyanate, dissolve them in 60mL of anhydrous THF, add 0.05g of DBTDL, and react at 60℃ for 5h to obtain a -NCO-terminated prepolymer solution.
[0055] (2) Introducing UPy: Weigh 2g of UPy-NH2, dissolve it in 15mL of DMSO, add the above prepolymer solution dropwise, and continue the reaction at 70℃ for 6h to obtain polyurethane containing UPy units (denoted as PU-UPy).
[0056] (3) Introducing disulfide bonds: Weigh 1g of 2,2′-dithiodiethanol and add it to the reaction system. React at 70℃ for 4h to introduce disulfide bonds into the polymer backbone. The final product is denoted as PU-UPy-SS.
[0057] Preparation of S4-2 composite membrane 0.75 g of PU-UPy-SS polymer was dissolved in 9.5 g of anhydrous THF to obtain a 5 wt.% polymer solution. 5 g of P-LLZTO powder was weighed and added to the polymer solution. The mixture was magnetically stirred for 12 h to allow the polymer to fully penetrate and encapsulate the modified particles. 0.05 g of the photoinitiator 2-hydroxy-2-methylphenylacetone was added, and stirring was continued for 30 min. The resulting slurry was poured into a polytetrafluoroethylene mold and cast into a film. The film was then vacuum dried at 50 °C for 6 h to remove the solvent. The dried film was then subjected to ultraviolet light (365 nm, power 10 mW / cm²). 2 Irradiation for 10 minutes under a light source causes the residual double bonds in the polymer to crosslink, enhancing network stability and yielding a solid electrolyte membrane, denoted as PU-LLZTO.
[0058] Comparative Example 1 The dense LLZTO ceramic sheet prepared in steps S1-3 of the example was used as the solid electrolyte membrane.
[0059] Comparative Example 2 The activated LLZTO powder from step S2 is directly pressed into sheets (cold pressing at 300 MPa) to obtain a solid electrolyte membrane.
[0060] Comparative Example 3 Take 4.5g of LLZTO powder prepared in steps S1-3 of Example 1, and dry ball mill it with 0.5g of PEO (molecular weight 1 million) for 2h. Hot press the mixed powder at 150℃ to form a film (thickness of about 80μm) to obtain a PEO / LLZTO composite film.
[0061] Comparative Example 4 Take 4.5g of LLZTO powder prepared in steps S1-3 of Example 1, mix it with 0.5g of PU-UPy-SS polymer synthesized in step S4-1, add THF solvent and stir to disperse. Then pour the resulting slurry into a polytetrafluoroethylene mold, cast it into a film, and dry it under vacuum at 50°C for 6h to remove the solvent, thus obtaining a solid electrolyte membrane.
[0062] Comparative Example 5 Commercial LLZO powder (99.9% purity, D50 = 1 μm) was purchased and dry-pressed into discs with a diameter of 20 mm (approximately 1 mm thick) at 200 MPa. The green blanks were placed in a magnesium oxide crucible covered with masterbatch powder and sintered at 1150 °C at a rate of 5 °C / min under air atmosphere for 12 h. The blanks were then cooled in the furnace to obtain dense LLZTO ceramic sheets.
[0063] The solid electrolyte membranes of Examples 1-3 and Comparative Examples 1-5 were assembled into coin cells. The assembly process is as follows: (1) Preparation of positive electrode: NCM811 positive electrode material, conductive carbon black and PVDF are mixed in a mass ratio of 90:5:5, NMP is added to make slurry, coated on aluminum foil, vacuum dried at 80℃ for 12h, and cut into 12mm diameter electrode sheets.
[0064] (2) Battery assembly: In an argon glove box (H2O, O2 < 0.1ppm), place the positive electrode shell, positive electrode plate, electrolyte membrane, lithium sheet (14mm diameter, 0.5mm thickness), gasket, spring, and negative electrode shell in sequence. For ceramic sheet electrolytes, add 2μL of ionic liquid (Pyr) to both sides before assembly. 13 FSI (Fixed Injection Seal) improves interface contact. It is sealed under 50 MPa pressure using a button cell sealing machine.
[0065] Resting and Testing: After assembly, allow the battery to stand for 12 hours, then perform electrochemical performance tests on the battery testing system. Voltage range: 2.8-4.3V (vs. Li). + / Li).
[0066] The performance test results are shown in Table 1: Table 1 Performance test results of the assembled batteries in Examples 1-3 and Comparative Examples 1-5 As shown in Table 1, Comparative Example 1, consisting of a pure dense LLZTO ceramic sheet electrolyte without any interface modification, retains the inherent defects of the garnet ceramic electrolyte, resulting in inferior performance across all indicators. The room temperature ionic conductivity is low (0.45 mS / cm) because the pure ceramic sheet contains a large number of low-conductivity impurities such as La2Zr2O7 and Li2CO3 at the grain boundaries, which become the main obstacle to lithium-ion bulk transport, leading to an extremely high grain boundary resistance. The lithium interface impedance is extremely high because the rigid ceramic and lithium metal have a "point-to-point" hard contact, resulting in numerous interface voids and poor lithiophilicity of the native LLZTO surface, drastically increasing the energy barrier for lithium-ion cross-interface transport. The critical current density is extremely low because poor interface contact leads to a high concentration of local current density, making it easy for lithium dendrites to grow and penetrate along grain boundaries / interface voids, causing rapid short circuits. The cycle life is extremely short because lithium dendrite penetration combined with the lack of stress buffering capacity in the ceramic sheet easily leads to grain boundary cracks during cycling, resulting in rapid electrolyte structure failure. The lack of self-healing ability and brittle mechanical properties are due to the absence of dynamic bonding structures in pure inorganic ceramics, making them unable to repair microcracks. Furthermore, their high brittleness and tendency to fracture under tension (fracture elongation <0.5%) render them unsuitable for practical battery processing applications. Poor capacity retention is caused by high interfacial impedance and lithium dendrite side reactions, resulting in low lithium-ion transport efficiency and rapid deactivation of active materials during battery charging and discharging.
[0067] Comparative Example 2 is a cold-pressed LLZTO powder sheet activated only by lattice oxygen, lacking a covalent anchoring layer and supramolecular network layer, thus failing to address issues of interfacial bonding, stress buffering, and structural stability. While plasma activation introduces oxygen vacancies, lowering the surface transport barrier and resulting in slightly higher ionic conductivity than pure ceramic sheets, the cold-pressed sheet exhibits low density, unresolved grain boundary impurities, and still hindered bulk transport, significantly lower than the examples. Although surface lithiophilicity is slightly improved by oxygen activation, the cold-pressed sheet remains a rigid inorganic structure, unresolved in its hard contact with lithium metal, and interfacial voids persist, leading to a still high interfacial impedance. The slight improvement in lithiophilicity alleviates localized current concentration, but without a flexible buffer layer, lithium dendrites still easily grow along grain boundaries, limiting its tolerance to low current densities, resulting in a low critical current density. Without an organic layer, the activated LLZTO particles only have physical contact; during cycling, volumetric stress causes particle delamination and rapid grain boundary crack propagation, leading to a short cycle life. Lacking a supramolecular dynamic bonding structure, it cannot repair micro-damage. The physical bonding of the cold-pressed sheet results in brittle mechanical properties and lack of processability. While improved surface ion transport efficiency leads to better capacity retention than pure ceramic sheets, the core issues of grain boundaries and interfaces remain unresolved. Lithium-ion transport efficiency continues to decline during cycling, resulting in generally poor capacity retention.
[0068] Comparative Example 3 used a traditional PEO / LLZTO physical hybrid composite membrane, employing a conventional physical coating modification strategy. This method lacks lattice oxygen activation and covalent anchoring; the polymer and ceramic particles are only physically adsorbed, resulting in the dual defects of weak interfacial bonding and low polymer conductivity. PEO itself has extremely low room temperature ionic conductivity (10⁻⁻⁴ Ω·cm). 5 ~10⁻ 4 (S / cm level), and physically mixed with LLZTO particles, lithium ion transport is easily hindered at the two-phase interface, resulting in the lowest overall conductivity among all groups. Although the flexibility of PEO improves the contact with lithium metal and reduces interfacial impedance, physical adsorption leads to micro-voids between the polymer and LLZTO particles, forming new transport resistance and resulting in high interfacial impedance. While PEO can buffer stress to some extent, its low conductivity limits the lithium ion transport rate, and the physical bond is prone to debonding, leaving the problem of local current concentration unresolved, resulting in a low critical current density. During cycling, PEO and LLZTO particles debond and separate due to volume stress, continuously increasing interfacial voids. At the same time, PEO is prone to side reactions with lithium metal, leading to rapid degradation of electrolyte performance and short cycle life. PEO is a linear polymer without dynamic hydrogen / disulfide bonds, which cannot repair interfacial micro-defects. Furthermore, the tensile strength of the physically mixed film is only 2.1 MPa, and the elongation at break is 15%, with both flexibility and strength far lower than the example, resulting in poor mechanical properties. Low ionic conductivity and polymer-ceramic phase separation result in extremely low lithium-ion transport efficiency during charging and discharging, continuous decline in the utilization rate of active materials, and poor capacity retention.
[0069] Comparative Example 4 shows a film of direct physical mixing of LLZTO powder and supramolecular polymer. Only a supramolecular network is introduced; there is no lattice oxygen activation or covalent anchoring layer. LLZTO and the supramolecular polymer are physically bonded, resulting in a high surface transport barrier and easy interface debonding. While the supramolecular polymer exhibits better ionic conductivity than PEO, the lack of lattice oxygen activation in LLZTO powder leads to a high transport barrier for lithium ions across the ceramic-polymer interface due to surface inert lattice oxygen. Furthermore, the presence of impurities at grain boundaries hinders bulk transport, resulting in lower ionic conductivity. The flexibility of the supramolecular network enables close contact with lithium metal, significantly reducing interfacial impedance. However, the physical adsorption of LLZTO and the polymer creates micropores at the interface, still presenting transport resistance and resulting in high interfacial impedance. The stress buffering capacity of the supramolecular network suppresses some lithium dendrite growth, but its physical bond with LLZTO is prone to debonding under high current, making it unable to withstand higher current densities. The dynamic bonding (hydrogen bonds + disulfide bonds) of the supramolecular network endows the film with a certain degree of structural stability, resulting in a cycle life far superior to the previous three comparative examples. However, the lack of covalent anchoring leads to easy separation at the ceramic-polymer interface, causing a continuous increase in interfacial impedance after long-term cycling and a poor cycle life. While the supramolecular polymer possesses self-healing capabilities, the absence of a covalent anchoring layer causes relative displacement between the ceramic and polymer during the repair process, preventing synchronous repair of the interface and the bulk, resulting in a self-healing efficiency far lower than the examples. The supramolecular network imparts a certain degree of flexibility and strength to the film, but physical mixing leads to weak internal bonding, and the mechanical properties remain lower than those of the gradient interface structure in the examples. The stable interface of the supramolecular network results in better capacity retention than traditional modification methods, but the high transport barrier on the LLZTO surface limits the transport efficiency of lithium ions at the ceramic-polymer interface.
[0070] Comparative Example 5 used commercial LLZO powder to sinter ceramic sheets without Ta / Nb co-doping, and the sintering process was not optimized. Its bulk conductivity and density were inferior to the LLZTO powder of this invention, and no interface modification was performed. Without Ta / Nb co-doping, the lithium-ion transport channels of the LLZO lattice were not effectively optimized, resulting in lower bulk ionic conductivity than the LLZTO ceramic sheet of this invention (Comparative Example 1). Furthermore, the commercial powder had a higher content of grain boundary impurities, leading to even lower ionic conductivity. Without interface modification, the rigid ceramic and lithium metal had a hard contact, and the commercial LLZO surface had poorer lithiophilicity, resulting in a much higher interface transport barrier than the examples, only slightly better than the pure LLZTO ceramic sheet of this invention (Comparative Example 1). The low bulk conductivity and poor interface contact exacerbated the problem of concentrated local current density, leading to a much higher risk of lithium dendrite penetration than the LLZTO-based electrolyte of this invention, and an extremely low critical current density. The lack of bulk defects due to the absence of doping and the lack of stress buffering due to the absence of interface modification caused the ceramic sheet to rapidly develop grain boundary cracks during cycling, resulting in electrolyte structural failure and an extremely short cycle life. Similar to pure LLZTO ceramic sheets, pure inorganic ceramics lack dynamic bonding structures, exhibiting brittle mechanical properties and no self-healing ability. They suffer from low bulk transport efficiency and high interfacial impedance, leading to severe lithium-ion loss during battery cycling, rapid capacity decay, and poor capacity retention.
Claims
1. A method for preparing a solid-state electrolyte membrane with a synergistic interface of lattice oxygen in-situ activation-organic covalent anchoring-supramolecular network, characterized in that, The method comprises the following steps: S1 Synthesis of Ta / Nb co-doped LLZO: S1-1 raw material mixing: in an argon glove box, Li 6.5 La3Zr 1.5 Ta 0.3 Nb 0.2 O 12 Li2CO3, La2O3, ZrO2, Ta2O5, Nb2O5 were weighed and ball-milled, and the obtained slurry was rotary evaporated to remove the solvent, vacuum dried, and sieved. S1-2 Calcination: after sieving, the powder is heated to 900-1000℃ in a muffle furnace, and kept for 4-5h; the calcined powder is ball milled again; S1-3 Molding and sintering: the powder is dry-pressed into a round sheet, heated to 1150-1200℃ in an air atmosphere, and kept for 12-14h for sintering; the sheet is cooled in the furnace to obtain a dense LLZTO ceramic sheet; the ceramic sheet is roughly crushed and ball milled to obtain LLZTO powder; S2 Lattice oxygen activation treatment: the LLZTO powder is laid in a quartz boat and placed in a plasma-enhanced chemical vapor deposition reaction chamber, and Ar and O2 mixed gas is introduced for plasma treatment; S3 Phosphonic acid anchor layer construction: amino propyl phosphonic acid and glycidyl methacrylate are dissolved in anhydrous THF, and triethylamine is added as a catalyst, and reacted at 50-60℃ for 6-8h to obtain a phosphonic acid derivative containing a double bond; the activated LLZTO powder in step S2 is dispersed in ethanol, and the phosphonic acid derivative containing a double bond is added, and stirred at 60-70℃ for 8-9h; after the reaction is completed, centrifugal separation is performed, washed with ethanol, and vacuum dried to obtain phosphonic acid anchor modified LLZTO powder; S4 Construction of supramolecular self-repairing network: S4-1 Supramolecular polymer synthesis: (1) Preparation of prepolymer: polyethylene glycol and isophorone diisocyanate are dissolved in anhydrous THF, and a catalyst dibutyltin dilaurate is added, and reacted at 60-70℃ for 4-5h to obtain a prepolymer solution terminated by -NCO; (2) Introducing UPy: UPy-NH2 is dissolved in DMSO, and the above prepolymer solution is added dropwise, and reacted at 60-70℃ for 6-8h to obtain a polyurethane containing UPy unit; (3) Introducing disulfide bond: 2,2'-dithiodiethanol is weighed and added to the reaction system, and reacted at 60-70℃ for 4-5h to obtain a supramolecular polymer; S4-2 Composite film preparation: the supramolecular polymer is dissolved in anhydrous THF to obtain a polymer solution; the phosphonic acid anchor modified LLZTO powder obtained in step S3 is added to the above polymer solution and stirred; add a photoinitiator and continue to stir to obtain a slurry; pour the slurry into a polytetrafluoroethylene mold, flow into a film, and vacuum dry to remove the solvent; irradiate the dried film under ultraviolet light to obtain a solid electrolyte film.
2. The method of making a solid-state electrolyte membrane with lattice oxygen in-situ activation-organic covalent anchoring-supramolecular network synergic interface as claimed in claim 1, wherein, In step S2, the volume ratio of Ar:O2 in the mixed gas is 4:1, the mixed gas flow is 50-60sccm, the working pressure is 50-60Pa, the radio frequency power is 150-160W, and the plasma treatment time is 30-60min.
3. The method of making a solid state electrolyte membrane with lattice oxygen in situ activation-organic covalent anchoring-supramolecular network synergic interface as claimed in claim 1, wherein, In step S3, the mass volume ratio of amino propyl phosphonic acid, glycidyl methacrylate, anhydrous THF and triethylamine is (5-10)g:(4-6)g:(50-60)mL:(0.5-1)mL.
4. The method of making a solid state electrolyte membrane with lattice oxygen in situ activation-organic covalent anchoring-supramolecular network synergic interface as claimed in claim 1, wherein, In step S3, the phosphonic acid derivative containing a double bond is 10-15% of the mass of the activated LLZTO powder in step S2.
5. The method of making a solid state electrolyte membrane with lattice oxygen in situ activation-organic covalent anchoring-supramolecular network synergic interface as claimed in claim 1, wherein, In step (1), the mass-to-volume ratio of polydiethanol, isophorone diisocyanate, catalyst dibutyltin dilaurate, and anhydrous THF is (200-250g): (40-50)g: 1g: (1000-1200)mL.
6. The method of making a solid state electrolyte membrane with lattice oxygen in situ activation-organic covalent anchoring-supramolecular network synergic interface of claim 1, wherein, In step (2), the mass-volume ratio of UPy-NH2, DMSO and the catalyst dibutyltin dilaurate in step (1) is (30-40) g: (200-300) mL: 1 g.
7. The method of making a solid state electrolyte membrane with lattice oxygen in situ activation-organic covalent anchoring-supramolecular network synergic interface as claimed in claim 1, wherein, In step (3), the mass ratio of 2,2′-dithiodiethanol to the catalyst dibutyltin dilaurate in step (1) is (15-20):
1.
8. The method of making a solid state electrolyte membrane with lattice oxygen in situ activation-organic covalent anchoring-supramolecular network synergic interface of claim 1, wherein, In step S4-2, the mass ratio of supramolecular polymer, phosphonic acid-anchored modified LLZTO powder to initiator is (10-15):(90-100):
1.
9. The method of making a solid state electrolyte membrane with lattice oxygen in situ activation-organic covalent anchoring-supramolecular network synergic interface of claim 1, wherein, In step S4-2, the photoinitiator is 2-hydroxy-2-methylphenylacetone.
10. A solid-state electrolyte membrane with lattice oxygen in-situ activation-organic covalent anchoring-supramolecular network synergistic interface, characterized in that, The solid electrolyte membrane with a lattice oxygen in-situ activation-organic covalent anchoring-supramolecular network synergistic interface as described in any one of claims 1-9 was prepared.
